Effect of care continuity on mortality of patients readmitted after colorectal surgery. Issue 5 (1st February 2019) - Justiniano, C. F.; Xu, Z.; Becerra, A. Z.; Aquina, C. T.; Boodry, C. I.; Temple, L. K.; Fleming, F. J.
Abstract : Background: Postoperative readmission after colorectal resection is common. It is unknown whether patients who receive readmission care from the surgeon who performed the index surgery have improved mortality. This study evaluated whether postdischarge continuity of care, defined at the hospital and surgeon level, was associated with decreased mortality after colorectal surgery. Methods: The Statewide Planning and Research Cooperative System was queried for patients who had colorectal resections from 2004 to 2014, and were readmitted within 30 days of discharge. Propensity‐adjusted logistic regression analysis was used to evaluate the association between 30‐day mortality and readmission care continuity. Results: A total of 20 016 patients readmitted within 30 days of discharge were eligible for analysis. Some 39·5 per cent of readmitted patients experienced hospital and surgeon care continuity, 47·1 per cent hospital but not surgeon continuity, 1·0 per cent surgeon but not hospital continuity, and 12·4 per cent neither hospital nor surgeon care continuity. A total of 1349 patients (6·7 per cent) died within 30 days of readmission. Patients readmitted with absence of surgeon but not of hospital care continuity had 2·04 (95 per cent c.i. 1·72 to 2·42) times the risk of 30‐day mortality compared with those who experienced surgeon and hospital continuity. Absence of both surgeon and hospital care continuity was associated with 2·65 (2·18 to 3·30) times the risk of death compared with presence of both. Conclusion: Readmission after colorectal resection not under the care of the index operating surgeon is associated with an increased risk of 30‐day mortality. Addressing processes of care that are affected by surgeon care continuity may decrease surgical deaths. Abstract : Continuity reduces mortality